Mineral content of shrubs from goat’s production systems in two seasons in an arid zone - Murillo Amador, Bernardo (Ecosistemas y Recursos Agropecuarios, 2023)
Minerals are needed in the diet of animals for maintenance, development, and reproduction. The objective was to determine mineral content of shrubs consumed by goats in an arid area from three production systems, during wet and dry seasons. Leaves, pods, stems, or flowers of 34 shrubs and one supplement were sampled manually and analyzed for Ca, Mg, K, Na, P, N, Fe, Mn, Zn, Cu, B, and Cl. The results showed that shrubs for all production systems had enough K Ca, K, Mg, Na, B, Cl and N for goat requirements; however, P was lower. The Zn, Cu, Fe, and Mn contents were lower in all shrubs. The results suggest that more non-legumes could be used in the goat diet in this arid area to enhance nutritional value because of their higher mineral content. Considering the status of mineral content, 58% of all minerals had higher content in the semi-intensive production system, and possibly, it is the best production system. Adequate values of mineral content were found in L. brevipes, T. lobaeformis and A. barclayana in the semi-intensive system, while in the extensive system the mineral content was of good nutritional quality with S. thurberi and C. gayana for the intensive system. The macro and minerals showed differences among the 35 shrubs and the nutritional quantity/quality of these minerals for goats varied depending on production system, season, and types of shrubs.